A device and method for preparing a diaphragm electrolysis water softening agent and a flocculant for an industrial circulating water system
Patent Information
- Application Number
- CN202611412191.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-11
- Publication Date
- 2026-10-27
AI Technical Summary
这种阳极钝化现象阻断了铁原子的进一步溶解,使得电絮凝过程难以为继,不仅电能转化为无用的热能,还使得系统完全丧失了絮凝净化能力
[0059]本发明引入隔膜屏障,突破了长期制约电絮凝技术的“碱性阳极钝化”与制约电沉积技术的“阴极极板结死垢”两大世界级工程难题。在完全无需外购及投加任何昂贵的阻垢剂、强酸强碱、PAC或FeCl3的条件下,仅以低廉的电能和易得的废铁板作为牺牲品,便实现了除硬、除硅与除悬浮物三效协同处理。
Smart Images

Figure CN122977642A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of industrial circulating water treatment technology, specifically relating to a device and method for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system. Background Technology
[0002] In modern industrial manufacturing, energy conversion, petrochemical, and metallurgical fields, circulating cooling water systems are core infrastructure for maintaining equipment thermal balance. Statistics show that industrial circulating cooling water systems typically account for 70% to 80% of total industrial water consumption. During the operation of cooling towers, inorganic salt crystals begin to nucleate and grow heterogeneously on the high-temperature surfaces of heat exchangers and pipe walls, forming dense inorganic calcium carbonate and magnesium hydroxide scale layers. The formation of these scale layers poses multifaceted hazards to industrial systems. First, inorganic scale, such as calcium carbonate, is an extremely poor thermal conductor, with a thermal conductivity only a fraction of that of carbon steel, leading to an exponential decrease in heat exchange efficiency and severely limiting industrial capacity. Second, the thickening of the scale layer significantly reduces the effective cross-sectional area of the pipes, increasing the hydraulic resistance of the fluid system and forcing the circulating water pumps to operate under higher loads, thus significantly increasing the system's energy consumption. More seriously, uneven scale deposition often triggers severe under-deposit corrosion, providing an ideal anaerobic environment for the reproduction of microorganisms such as sulfate-reducing bacteria (SRB), which may ultimately lead to perforation and failure of the heat exchange tube bundle, resulting in catastrophic safety accidents.
[0003] To address these serious challenges, traditional industrial circulating water treatment solutions primarily rely on large-scale chemical dosing. This traditional "chemical-driven" model is facing insurmountable bottlenecks under current environmental regulations and economic efficiency requirements. The long-term accumulation of chemicals not only increases the conductivity and salinity of circulating water, causing secondary pollution, but also makes the composition of the system's effluent extremely complex, significantly increasing the difficulty and cost of subsequent wastewater treatment. Globally, zero-liquidity discharge and stringent phosphorus emission limits are forcing industry to seek greener, more efficient, and economical alternatives.
[0004] To reduce reliance on chemical reagents, electrochemical water treatment technology offers an environmentally friendly alternative. This technology achieves the separation and degradation of pollutants without the need for additional chemical additives and is mainly divided into two categories: electrochemical precipitation and electrocoagulation. However, when these technologies are applied independently to extremely complex industrial circulating water systems, they each reveal significant technical shortcomings. Traditional electrochemical precipitation technology (i.e., electrochemical softening) primarily utilizes the water reduction reaction (hydrogen evolution reaction) and dissolved oxygen reduction reaction on the cathode surface. Its fatal flaw lies in the rapid covering and enveloping of the entire cathode surface by a dense scale layer (i.e., cathode passivation), drastically reducing the effective conductive area of the electrode, leading to a sharp increase in cell voltage and a precipitous drop in current efficiency. Although researchers have attempted to remove the scale layer using methods such as polarity reversal, this not only increases the complexity of the power supply system but also accelerates the aging and wear of the electrode materials. Traditional diaphragm-less electrocoagulation technology uses soluble metals such as iron or aluminum as the anode. Under direct current, the sacrificial anode undergoes oxidation and dissolution, releasing metal cations (such as Fe). 2+ and Fe 3+ These ions undergo multi-stage hydrolysis in water to form hydroxide flocs with extremely strong adsorption and sweeping capabilities, used to remove suspended solids, colloidal silicon, and heavy metals from water. However, when traditional iron anode electrocoagulation is directly used to treat high-hardness, high-alkalinity industrial circulating cooling water, the lack of physical isolation within the reactor leads to a large amount of OH- produced at the cathode... - It will rapidly migrate and diffuse towards the anode region. When the localized high concentration of Fe on the anode surface... 3+ Encountering high concentrations of OH - At this time, a dense and non-conductive ferric hydroxide passivation film is instantly formed and firmly adheres to the surface of the iron anode. This anodic passivation phenomenon blocks the further dissolution of iron atoms, making the electrocoagulation process unsustainable. Not only is electrical energy converted into useless heat energy, but the system also completely loses its flocculation and purification capabilities. Summary of the Invention
[0005] To address the dual technical barriers of traditional electrochemical precipitation for cathode scaling and traditional electrocoagulation for anode passivation, this invention provides a device and method for preparing a synergistic flocculant for hardening removal in industrial circulating water systems via diaphragm electrolysis. Using a "diaphragm electrolysis system" as the core platform, it innovatively combines two major processes: "sacrificial dissolution of the iron anode" and "efficient hardening removal and crystallization at the cathode." Through the physical isolation of the medium, a dual microenvironment of extreme alkalinity at the cathode and extreme acidity at the anode is artificially created and maintained within a single reactor. This achieves the ultimate synergistic effect of hardness removal and the generation of highly active iron flocculants during the effluent recombination stage.
[0006] To achieve the above objectives, the present invention employs the following technical solution:
[0007] This invention provides an industrial circulating water system diaphragm electrolysis synergistic flocculant preparation device, comprising a circulating water inlet pipe, an electrolysis reactor, and a power supply. A diaphragm is disposed inside the electrolysis reactor, dividing it into a cathode chamber and an anode chamber. An anode assembly is disposed in the anode chamber, and a cathode assembly is disposed in the cathode chamber. The positive terminal of the power supply is connected to the anode assembly, and the negative terminal is connected to the cathode assembly. The electrolysis reactor is provided with a cathode chamber inlet, a cathode chamber outlet, an anode chamber inlet, and an anode chamber outlet. The circulating water inlet pipe is connected to the cathode chamber inlet and the anode chamber inlet respectively via a flow distribution regulating valve. The cathode chamber outlet is connected to the inlet of a hydrocyclone separator, the anode chamber outlet is connected to the first inlet of a flocculation tank, the outlet of the hydrocyclone separator is connected to the second inlet of the flocculation tank, and the outlet of the flocculation tank is connected to a filter.
[0008] Furthermore, the diaphragm is made of porous polymer microporous membrane, ceramic diaphragm, or ion exchange membrane.
[0009] Furthermore, the porous polymer microporous membrane is a woven mesh or nonwoven nonwoven fabric made of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride or polysulfone that has been hydrophilically modified; the ceramic diaphragm is an alumina or silicon carbide microporous ceramic diaphragm; and the ion exchange membrane is a cation exchange membrane or anion exchange membrane.
[0010] Furthermore, the anode assembly is made of pure iron plate, low carbon steel plate, cast iron mesh or iron alloy, and its structure is designed as plate-shaped solid, multi-layer perforated plate, staggered wire mesh or consumable rod array.
[0011] Furthermore, the cathode assembly is made of corrosion-resistant stainless steel, titanium-based materials, high specific surface area carbon felt or graphite felt, and its structure is designed as a three-dimensional mesh structure, multi-layer stacked metal wire mesh or perforated corrugated plate.
[0012] This invention also provides a method for preparing a synergistic flocculant for diaphragm electrolytic dehardening in industrial circulating water systems, comprising the following steps:
[0013] S1. Industrial water containing scale-forming ions is diverted and continuously fed into the cathode chamber and anode chamber respectively, with the volume of liquid flowing into the cathode chamber being greater than the volume flowing into the anode chamber.
[0014] S2. Apply a DC bias voltage to the cathode and anode components, controlling the apparent current density to be 6 mA / cm². 2 Up to 40 mA / cm 2Between these two states, in the cathode chamber, a reduction reaction occurs, causing the pH to rise above 10.5, promoting the precipitation of scale-forming ions; simultaneously in the anode chamber, a trace oxygen evolution reaction is controlled, and protons accumulate in the anode chamber due to the barrier of the diaphragm, maintaining the pH below 6.0, inducing the continuous dissociation of Fe from the anode. 2+ and Fe 3+ ;
[0015] In step S2, the current density is the key factor controlling the crystallization precipitation rate and the Faraday metal dissolution rate. Too low a current density will prevent the cathode from accumulating sufficient OH groups. - The concentration is too high to overcome the solubility product barrier of substances such as Mg(OH)2; at the same time, iron deposition at the anode is slow, preventing the formation of effective flocculation. Excessively high current densities (e.g., exceeding 100 mA / cm²) are also problematic. 2 This can lead to severe electrode polarization and an exponential increase in cell voltage. On the anode side, a violent oxygen evolution reaction can take over, greatly reducing the current efficiency of iron dissolution.
[0016] Current density at 6 mA / cm 2 Up to 40 mA / cm 2 Within this range, not only is the electrochemical precipitation rate and diffusion kinetics of calcium carbonate optimally balanced, but the dissolution Faraday efficiency of the iron anode can also be maintained above 90%, ensuring that the system's energy efficiency ratio is at its best.
[0017] S3. Guide the scale-containing catholy liquid away from the electrolysis reactor for physical pre-separation to remove most of the hardness crystal clusters;
[0018] S4. Mix the physically pre-separated catholy and anolyte, utilizing the automatic acid-base neutralization property of the fluids to adjust the pH back to near neutral, triggering Fe... 2+ Rapid air self-oxidation and subsequent explosive generation of ferric hydroxide polymer network, through electrostatic adsorption and sweeping flocculation network, trap and capture micro-nano scale particles that have not settled completely, colloidal silica and suspended macromolecular organic matter in the water.
[0019] S5. The mixture from S4 is filtered and collected to retain the flocculated flocs as a flocculant, while clean water is obtained and returned to the main cooling water circulation path.
[0020] Furthermore, the volume ratio of liquid flowing to the cathode chamber to the anode chamber is 6:4 to 9:1, and the residence time in the cathode and anode chambers is between 5 and 20 minutes. The residence time and distribution ratio of the fluid in the reactor directly affect the ion concentration gradient and the final result of acid-base neutralization. This invention abandons the series flow mode where water flows through one chamber before entering another, and forces an independent parallel flow configuration. The cathode undertakes the heavy task of hardening, distributing the vast majority (70% to 80%) of the circulating water, which not only softens the main water body to the maximum extent, but also absorbs a large amount of OH-. - To prevent premature crystallization and reactor blockage; the anode only acts as a generator, and a small amount of water (20%~30%) is allocated to allow the Fe released by electrolysis to... 2+ and H + A higher concentration peak is achieved within this small volume of fluid. The high concentration of acidic molten iron provides stronger explosive flocculation dynamics in the subsequent recombining and mixing stage. In addition, the small level pressure difference generated by this flow difference also helps to overcome transmembrane leakage losses caused by the electroosmotic drag of water molecules.
[0021] The effective contact time (HRT) of circulating water in the electrolysis zone determines the depth of the reaction. For a single-stage diaphragm electrolysis reactor, the hydraulic residence time is between 5 and 20 minutes. For extremely hard water or water with abnormally high silica content, this invention supports extending the total HRT through multi-stage series connection, thereby achieving deep softening and deep desiliconization by repeatedly cutting the hardness degradation curve.
[0022] Furthermore, the anode assembly is made of pure iron plate, low-carbon steel plate, cast iron mesh, or iron alloy, and its structure is designed as a plate-shaped solid, a multi-layer perforated plate, an interlaced wire mesh, or a consumable rod array; it serves as a sacrificial anode to continuously provide an iron source. The plate-shaped design facilitates online plug-and-play replacement when the electrode is depleted. The mesh structure helps increase the surface area and promotes the uniform distribution of acidic products.
[0023] The cathode assembly utilizes corrosion-resistant stainless steel, titanium-based materials, or high-specific-surface-area carbon felt or graphite felt, with a three-dimensional mesh structure, multi-layered stacked metal wire mesh, or perforated corrugated plates. The high three-dimensional specific surface area disperses the apparent current, reduces the actual local current density, and significantly delays the nucleation of dense scale. The porous three-dimensional structure can accommodate a large amount of precipitated soft scale without being physically blocked. The cathode must possess an extremely low hydrogen evolution overpotential to accelerate gas generation and descaling.
[0024] Furthermore, the diaphragm is made of porous polymer microporous membrane, ceramic diaphragm, or ion exchange membrane.
[0025] Furthermore, the porous polymer microporous membrane is made of woven or nonwoven fabric of hydrophilically modified polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, or polysulfone. The average pore size of the cross-section must be strictly controlled between 0.05 μm and 2.0 μm. If the pore size is too small, it will hinder the migration of hydrated ions and result in excessively high cell voltage; if the pore size is too large, it will be unable to prevent the macroscopic convection of fluids from disrupting the microenvironment. At the same time, the porosity is between 25% and 80%.
[0026] For industrial circulating cooling systems containing a large number of sharp abrasive particles or with highly oxidizing and extreme water quality, ceramic diaphragms can be selected. The ceramic diaphragms are made of alumina or silicon carbide microporous ceramic diaphragms with controllable pore size, providing superior mechanical strength and chemical corrosion resistance.
[0027] The ion exchange membrane is either a cation exchange membrane (CEM) or an anion exchange membrane (AEM). For example, when a CEM is used, only cations are allowed to pass through, completely blocking OH groups. - Permeation into the anode causes the pH in the cathode chamber to rise to the crystallization point at a faster rate, resulting in more extreme hardness removal performance (removal rate can be increased to over 80%).
[0028] The physicochemical mechanism of synergistic hardening and flocculation by membrane electrolysis in this invention is as follows:
[0029] (1) Construction of alkaline microenvironment in cathode chamber and mechanism of active hardness-induced precipitation
[0030] In the cathode chamber separated by the diaphragm electrolysis reactor, a series of complex electrochemical and thermodynamic phase transition processes unfold as industrial circulating cooling water (catholytic liquid) containing high concentrations of calcium and magnesium ions and bicarbonates flows across the cathode surface.
[0031] The first is the dominant reduction reaction on the cathode surface, namely the reduction of water molecules and dissolved oxygen:
[0032] 2H₂O + 2e⁻ → H₂ + 2OH⁻ -
[0033] O₂ + 2H₂O + 4e⁻ → 4OH⁻ -
[0034] The presence of a membrane (e.g., a porous polymer membrane with a pore size of 0.05 to 2.0 micrometers) in the system effectively restricts macroscopic convection mixing of the fluid and significantly reduces the rate of back-diffusion of ions between the anode and cathode. Therefore, the large amount of OH generated by the cathode reaction... -The calcium carbonate is trapped inside the cathode chamber, causing a significant increase in the pH of the boundary layer near the cathode surface and even the entire cathode chamber solution. According to thermodynamic phase diagrams and related experimental data, the solution pH needs to be stable above 10.5 to achieve efficient precipitation of calcium carbonate; while to induce the precipitation of brucite (magnesium hydroxide), the pH needs to be further reached and maintained at around 11.5 or even 13.0.
[0035] In this highly alkaline microenvironment, the chemical balance of the carbonic acid system within the water body is completely disrupted:
[0036] HCO3 - + OH - →CO3 2- +H2O
[0037] Subsequently, the supersaturated scale-forming ions overcame the nucleation barrier, resulting in intense homogeneous and heterogeneous nucleation reactions:
[0038] Ca 2+ +CO3 2- →CaCO3
[0039] Mg 2+ +2OH - →Mg(OH)2
[0040] One of the core design features of this invention is the abandonment of the outdated approach of depositing scale on the cathode plate and then scraping it off. Instead, through the design of a three-dimensional mesh structure of the cathode and appropriate hydraulic flow velocity, combined with the "air flotation and stripping effect" of tiny hydrogen (H2) bubbles precipitated on the cathode surface, the large amount of micro-nano-sized calcium carbonate and magnesium hydroxide crystals cannot firmly adhere to the cathode surface, but instead remain free in the catholyte as loose suspended particles (soft scale). This mechanism ensures that the cathode surface maintains extremely high electrochemical activity at all times, and the current density does not decay over time. The catholyte effluent containing a large amount of soft scale suspension is then guided to an external hydrocyclone or coarse sedimentation tank for the first stage of solid-liquid separation.
[0041] 2) Construction of acidic microenvironment in the anode chamber and in-situ dissolution mechanism for preventing passivation of iron anode
[0042] The fatal flaw of traditional ferroelectric flocculation technology lies in alkaline passivation, but this invention completely reverses this situation by utilizing a diaphragm. Within the anode chamber, physically isolated by the diaphragm, OH radicals from the cathode cannot be obtained... - Neutralization occurs on the surface of the anode plate, where a series of unique reactions take place that are crucial for flocculant preparation.
[0043] When used as a sacrificial anode, the iron-based material (pure iron or low-carbon steel) undergoes a dominant anodic metal dissolution reaction under anodic polarization potential, following Faraday's law of electrolysis.
[0044] Fe →Fe 2+ +2e-
[0045] At the same time, in order to achieve the design goals of this system, it is necessary to allow and appropriately control the occurrence of partial oxygen side reactions:
[0046] 2H₂O→O₂+4H + +4e-
[0047] In traditional understanding, the oxygen evolution reaction (OER) is considered a negative factor, consuming additional electrical energy and reducing current efficiency. However, in the system of this invention, it is the core driving force for maintaining the continuous operation of the system. This is because the OER releases a large number of protons (H+). + Under the physical barrier of the diaphragm, these H... + Unable to react with OH at the cathode - The pH of the anode chamber is neutralized and continuously accumulated in the anolyte, causing the pH to drop rapidly and remain stable below 6.0 for a long period, forming a highly acidic microenvironment.
[0048] This self-sustaining acidic microenvironment has extremely important technological value: it completely disrupts the thermodynamic conditions for the formation of passivation films of ferric hydroxide (Fe(OH)3) or hydrated ferric oxide. Under acidic conditions, the iron surface remains exposed and exhibits extremely high electrochemical activity, allowing the iron dissolution reaction at the anolyte to proceed continuously with near-100% Faraday efficiency. The iron ions dissolved in the water primarily exist as free Fe... 2+ and some Fe 3+ It exists stably and at high concentrations in the acidic anolyte effluent. This solution, rich in activated iron ions and protons and free from any added chemical contamination, constitutes an extremely high-quality "in-situ acidic iron flocculant precursor".
[0049] 3) Synergistic effect of effluent recombination and derived high-efficiency sweeping flocculation network
[0050] Simply separating the cathode and anode only completes the first step in hardening and iron production. The true synergistic climax of this invention occurs at the confluence of fluids outside the electrolytic reactor.
[0051] When the high-pH, high-alkalinity cathode effluent, which has undergone preliminary solid-liquid separation (removing most of the visible crystal particles), re-merges with the low-pH anode effluent, which is rich in iron ions and protons, in a specific static mixer or flocculation tank, a chain of physicochemical cascade reactions will be triggered:
[0052] Spontaneous acid-base neutralization mechanism: The H⁺ accumulated in the anolyte due to the micro-oxygen evolution reaction reacts with the OH⁻ in the catholyte that has not been completely precipitated and consumed. -Extremely rapid acid-base neutralization occurs. Without relying on any external acid-base adjusters, the pH of the mixed system automatically corrects to a slightly alkaline range of 7.5 to 8.5. This self-buffering effect is extremely beneficial to industrial cooling water networks, eliminating scaling tendencies and preventing acid corrosion.
[0053] Instantaneous oxidation of iron ions and polynuclear polymerization network: As the system pH returns to the neutral or even weakly alkaline range, and the circulating water contains a large amount of saturated dissolved oxygen, the anode effluent carries a large amount of free Fe. 2+ It will undergo spontaneous oxidation, transforming into highly reactive Fe. 3+ With the increase of pH, Fe 3+ It rapidly exceeds its solubility limit, undergoing multi-stage deep hydrolysis reactions:
[0054] 4Fe 2+ +O2+2H2O+8OH - →4Fe(OH)3
[0055] During this dynamic and brief phase transition window, high charge density products are formed, including hydrated iron oxides (such as pyrite γ-FeOOH), verdigris (a layered bimetallic hydroxide containing Fe(II) and Fe(III)), and complex polyhydroxy iron complexes.
[0056] The ultimate purification through heterogeneous sweeping flocculation: These newly formed polynuclear iron hydroxide complexes possess an unparalleled large specific surface area and extremely strong charge neutralization ability. They spread and intertwine in the water to form a vast flocculation network, tightly encapsulating residual nanoscale calcium carbonate seeds, pre-existing colloidal substances, silica (a key precursor to silicate scaling), and even suspended organic macromolecules and microbial slime in the cathode effluent through a "sweeping action" and "netting" mechanism.
[0057] Ultimately, these large, densely structured "flocs" are easily intercepted in subsequent multi-media filters or shallow sand filters. This mechanism achieves a one-stop, synergistic removal of water hardness, suspended turbidity, silica, and organic matter. Through this bypass treatment architecture, the system can achieve up to 95% silica removal and 40%–60% removal of total calcium and magnesium hardness—a comprehensive purification level that no single traditional process can reach.
[0058] Compared with the prior art, the present invention has the following advantages:
[0059] This invention introduces a membrane barrier, overcoming two major world-class engineering challenges that have long constrained electrocoagulation technology: "alkaline anode passivation" and "cathode plate dead scale" that have constrained electrodeposition technology. Without requiring the purchase or addition of any expensive scale inhibitors, strong acids or alkalis, PAC, or FeCl3, and using only inexpensive electricity and readily available scrap iron plates as sacrificial materials, it achieves a synergistic treatment of hardening, silicon removal, and suspended solids removal. Attached Figure Description
[0060] Figure 1 A schematic diagram of a device for preparing diaphragm electrolytic dehardening synergistic flocculant for industrial circulating water systems.
[0061] Figure 2 A flowchart for the preparation method of diaphragm electrolytic dehardening synergistic flocculant for industrial circulating water systems. Detailed Implementation
[0062] To further illustrate the technical solution of the present invention, the present invention will be further described below through embodiments.
[0063] Example 1
[0064] like Figure 1 As shown in this embodiment, an industrial circulating water system diaphragm electrolysis synergistic flocculant preparation device includes a circulating water inlet pipe 1, an electrolysis reactor 3, and a power supply 7. A diaphragm 6 is installed inside the electrolysis reactor 3, dividing the electrolysis reactor 3 into a cathode chamber and an anode chamber. An anode assembly 4 is installed in the anode chamber, and a cathode assembly 5 is installed in the cathode chamber. The positive terminal of the power supply 7 is connected to the anode assembly 4, and the negative terminal of the power supply 7 is connected to the cathode assembly 5. The electrolysis reactor 3 is provided with a cathode chamber inlet, a cathode chamber outlet, an anode chamber inlet, and an anode chamber outlet. The circulating water inlet pipe 1 is connected to the cathode chamber inlet and the anode chamber inlet respectively through a flow distribution regulating valve 2. The cathode chamber outlet is connected to the inlet of a cyclone separator 8, the anode chamber outlet is connected to the first inlet of a flocculation tank 9, the outlet of the cyclone separator 8 is connected to the second inlet of the flocculation tank 9, and the outlet of the flocculation tank 9 is connected to a filter 10.
[0065] Example 2
[0066] This embodiment mainly targets the circulating water system of large and medium-sized chemical plants with cooling tower capacity ranging from 1000m3 / h to 5000m3 / h.
[0067] The raw water to be treated was taken from a chemical plant's highly concentrated industrial circulating cooling water. Its initial water quality indicators were: total hardness (as CaCO3) 750 mg / L (of which Ca... 2+ Approximately 600 mg / L, Mg 2+Approximately 150 mg / L); soluble silica (SiO2) 50 mg / L; suspended solids (SS) and turbidity 15 NTU; conductivity 2500 μS / cm; pH 8.2.
[0068] A booster pump draws approximately 5% to 10% of the total circulating volume of bypass water from the cooling tower's cold water basin or the main return water pipeline. The water first passes through a 200-micron-level automatic self-cleaning disc filter to intercept large particles such as leaves and sediment, preventing blockage of the subsequent precision diaphragm.
[0069] like Figure 2 As shown in this embodiment, a method for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system includes the following steps:
[0070] S1. Flow field establishment:
[0071] The pre-filtered bypass water (industrial water containing scale-forming ions) is diverted through the flow distribution regulating valve 2, and continuous water flows are introduced into the cathode chamber and the anode chamber respectively. The volume of liquid flowing into the cathode chamber is greater than that flowing into the anode chamber, and the volume ratio is 7.5:2.5. The hydraulic retention time (HRT) is controlled at 10 minutes.
[0072] 75% of the bypass water is introduced into the cathode chamber equipped with a 316L stainless steel three-dimensional perforated mesh plate (stacked in 3 layers to provide a large specific surface area), and 25% of the bypass water is injected into the anode chamber equipped with a 3mm pure iron plate array. The cathode chamber and the anode chamber are separated by a hydrophilically modified polytetrafluoroethylene (PTFE) porous membrane with an average pore size of 0.5 μm and a porosity of 60%. The electrode distance between the electrode and the membrane is set to 1.0 cm.
[0073] The electrolysis reactor is a single-stage rectangular flow channel type, with an effective electrolysis area of 1.0 m². 2 .
[0074] S2, Microenvironment Construction and Electrolysis-Driven Development:
[0075] A constant DC power supply (DC bias voltage) is applied to the cathode and anode assemblies to maintain the apparent current density of the electrode control at 25 mA / cm². 2 Under these conditions, the tank voltage remains stable at around 6.5 V.
[0076] Within the cathode chamber, reduction occurs on the cathode surface, releasing H2 and a large amount of OH. - This causes the local pH of the catholyte to rise to 11.2, which in turn causes calcium and magnesium ions to precipitate as calcium carbonate and magnesium hydroxide scale, resulting in a large amount of visible white turbidity in the water (mainly calcium carbonate and magnesium hydroxide scale crystals).
[0077] Simultaneously, within the anode chamber, controlling the trace oxygen evolution reaction allows H... + Fe accumulates in the anode chamber due to the barrier effect of the diaphragm, forcing the pH of the anode microenvironment to be maintained at approximately 3.5, thus inducing the iron anode to continuously dissociate into a non-passivated free state. 2+ and Fe 3+ This produces a highly concentrated pale green / slightly yellow acidic iron ion solution (containing a large amount of Fe). 2+ and a small amount of Fe 3+ ).
[0078] S3, Primary Descaling:
[0079] The scale-laden catholyte is guided out of the electrolysis reactor for physical pre-separation, removing most of the hard crystal clusters. Specifically, the fluid in the cathode chamber enters the hydrocyclone separator directly through a short pipe, where centrifugal force separates approximately 70% of the large inorganic particles and discharges them into the bottom sludge hopper, while a clear liquid containing fine crystal nuclei and residual alkalinity overflows from the top.
[0080] S4, Recombination, self-neutralization, and sweeping flocculation:
[0081] The catholy solution after primary descaling (still containing alkalinity and tiny crystal nuclei) is simultaneously discharged into a "static mixing" flocculation tank equipped with baffles for mixing with the acidic anolyte rich in iron ions and protons. Within the flocculation tank, the pH is adjusted to near neutral (pH=7.8) by utilizing the automatic acid-base neutralization properties of the fluids, triggering the Fe... 2+ The rapid air self-oxidation and subsequent explosive generation of ferric hydroxide polymer network, through electrostatic adsorption and sweeping flocculation network, capture and trap micro- and nano-scale particles that have not completely settled, colloidal silica and suspended macromolecular organic matter in the water.
[0082] Specifically, in the flocculation tank, a large amount of Fe 2+ It is rapidly oxidized to Fe by the high oxygen content of the circulating water. 3+ As the deep reddish-brown iron hydroxide / green rust multinuclear network system rapidly forms, the tiny calcium carbonate crystals that originally escaped separation by the hydrocyclone separator, the free colloidal silica enriched in the water, and some large organic molecules are completely captured and swept up by the huge floc network, forming large floc particles.
[0083] S5, Point-of-use water purification:
[0084] The reconstituted water after S4 flocculation flows by gravity into a multi-media filter (or shallow sand filter) for filtration and collection. Large, dense, reddish-brown iron-based composite flocs are retained as flocculants, while the effluent is transformed into high-quality pure water with extremely low hardness and near-zero turbidity, which is directly returned to the cooling tower water tank. The filter is backwashed periodically using differential pressure, and high-concentration sludge is pumped into a plate and frame filter press for dewatering.
[0085] To objectively verify whether the present invention (diaphragm-assisted iron electrolysis) can solve the core technical problem of "anodic passivation" and simultaneously achieve the claimed technical effects of "hardening removal" and "deep purification through the preparation of iron flocculants", the following comparative experiment was set up.
[0086] (1) Experiment setup and grouping:
[0087] All experiments used the raw water to be treated described in Example 2 above (total hardness 750 mg / L, SiO2 50 mg / L, turbidity 15 NTU), and the effect was evaluated by continuous operation for 72 hours.
[0088] This invention employs the complete apparatus and procedures of Example 2 (diaphragm system, current density 25 mA / cm²). 2 The positive and negative flow ratio is 7.5:2.5, and the effluent is re-filtered.
[0089] Comparative Example 1 (Traditional Membrane-less Ferroelectric Flocculation): The PTFE diaphragm in the device was removed, and the anode and cathode were placed in the same reaction chamber, using the same iron anode and stainless steel cathode. The influent flow was continuous, with a total flow rate of 1000 L / h. The initial current density was also set at 25 mA / cm². 2 The effluent directly enters the flocculation sedimentation and filtration unit.
[0090] Comparative Example 2 (Traditional Chemical Softening Method): No electrolysis device was used. NaOH was directly added to 1000 L / h of raw water to adjust the pH to 11.0 to precipitate hardness, followed by the addition of 200 mg / L of polyferric chloride (PFC) as a chemical flocculant. Finally, the pH was adjusted and the water was filtered.
[0091] (2) Comparison table of experimental data and results:
[0092] Initial operating tank voltage (T=0h) 6.5 V 5.8 V N / A (No power consumption) Final operating tank voltage (T=72h) 6.6 V (Extremely stable) 24.5 V (severe and rapid increase) N / A Surface condition of iron anode (T=72h) It has a uniform metallic luster and is free of any adhering substances. The surface is firmly coated with a dense layer of hard, reddish-brown and white mixed scale, with a thickness greater than 2mm (completely passivated). N / A Total hardness removal rate (average effluent) 68.5% (decreased to approximately 236 mg / L) 12.4% (Processing essentially failed) 71.2% <![CDATA[Silicate (SiO2) removal rate]]> 95.2% (reduced to <2.5 mg / L) 22.1% 55.4% Effluent turbidity (NTU) <0.5 NTU 12 NTU (No effective floc formation) <1.0 NTU New impurity ions in the effluent No new debt ion none <![CDATA[Massive introduction of Na + and Cl - leads to a sharp surge in conductivity]]> <![CDATA[Comprehensive energy consumption (converted per 1kg of CaCO₃ removed)]]> Approximately 3.17 kWh / kg The efficiency increases rapidly to >15 kWh / kg over time. The reagents are extremely expensive and generate large amounts of hazardous chemical sludge.
[0093] As can be seen from Table 1, this invention completely solves the problem of "alkaline passivation of iron anode": the data from Comparative Example 1 shows that, under conditions without a diaphragm, the OH generated at the cathode... - Inevitably, the flux diffuses to the anode. After only a few hours of operation, a dense layer of Fe(OH)3 and calcium carbonate composite insulating scale forms on the iron anode surface, causing the cell voltage to surge from 5.8V to the system's limit voltage of 24.5V, almost interrupting the current. However, during 72 hours of continuous high-load operation, the cell voltage of this invention remained stable at 6.5~6.6V, and the iron electrode surface remained pristine. This experimental data demonstrates that the diaphragm successfully locks in H+. + A self-cleaning acidic microenvironment with pH < 4 was constructed in the anode chamber, achieving 100% passivation prevention effect.
[0094] Verification of the synergistic effect of hardening removal and in-situ flocculation: Under conditions without the addition of any external chemical agents, this invention induces calcium carbonate and brucite scale at a high pH at the cathode, and then utilizes the activated Fe generated by the unpassivated iron anode. 3+ Sweeping and flocculation were performed. Experimental data showed that the total hardness was removed by 68.5%, and in particular, a deep stripping of SiO2, which causes fatal damage to silica scale, was achieved at a depth of up to 95.2%. Compared with Comparative Example 2 (chemical method), which also removes hardness, this invention not only eliminates the expensive cost of chemical dosing, but also avoids the vicious cycle of a surge in the conductivity and corrosive salts of circulating water caused by the addition of NaOH and iron salts.
[0095] The foregoing has shown and described the main features and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0096] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A device for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system, characterized in that, The system includes a circulating water inlet pipe (1), an electrolysis reactor (3), and a power supply (7). A diaphragm (6) is installed inside the electrolysis reactor (3), dividing the reactor (3) into a cathode chamber and an anode chamber. An anode assembly (4) is installed in the anode chamber, and a cathode assembly (5) is installed in the cathode chamber. The positive terminal of the power supply (7) is connected to the anode assembly (4), and the negative terminal of the power supply (7) is connected to the cathode assembly (5). A cathode chamber inlet and a cathode chamber outlet are provided on the electrolysis reactor (3). The anode chamber inlet and anode chamber outlet are connected to the cathode chamber inlet and anode chamber inlet respectively via a flow distribution regulating valve (2). The cathode chamber outlet is connected to the inlet of the hydrocyclone separator (8). The anode chamber outlet is connected to the first inlet of the flocculation tank (9). The outlet of the hydrocyclone separator (8) is connected to the second inlet of the flocculation tank (9). The outlet of the flocculation tank (9) is connected to the filter (10). The diaphragm (6) is made of porous polymer microporous membrane, ceramic diaphragm and ion exchange membrane.
2. The apparatus for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system according to claim 1, characterized in that, The porous polymer microporous membrane is a woven mesh or nonwoven nonwoven fabric made of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride or polysulfone that has been hydrophilically modified; the ceramic diaphragm is an alumina or silicon carbide microporous ceramic diaphragm; the ion exchange membrane is a cation exchange membrane or anion exchange membrane.
3. The apparatus for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system according to claim 1, characterized in that, The anode assembly (4) is made of pure iron plate, low carbon steel plate, cast iron mesh or iron alloy, and its structure is designed as plate solid, multi-layer perforated plate, interlaced wire mesh or consumable rod array.
4. The apparatus for preparing a diaphragm electrolytic dehardening synergistic flocculant for an industrial circulating water system according to claim 1, characterized in that, The cathode assembly (5) is made of corrosion-resistant stainless steel, titanium-based material, high specific surface area carbon felt or graphite felt, and its structure is designed as a three-dimensional mesh structure, multi-layer stacked metal wire mesh or perforated corrugated plate.
5. A method for preparing a synergistic flocculant for diaphragm electrolysis dehardening in an industrial circulating water system, characterized in that, Includes the following steps: S1. Industrial water containing scale-forming ions is diverted and continuously fed into the cathode chamber and anode chamber respectively, with the volume of liquid flowing into the cathode chamber being greater than the volume flowing into the anode chamber. S2. Apply a DC bias voltage to the cathode and anode components, controlling the apparent current density to be 6 mA / cm². 2 Up to 40mA / cm 2 Between these two states, in the cathode chamber, a reduction reaction occurs, causing the pH to rise above 10.5, promoting the precipitation of scale-forming ions; simultaneously in the anode chamber, a trace oxygen evolution reaction is controlled, and protons accumulate in the anode chamber due to the barrier of the diaphragm, maintaining the pH below 6.0, inducing the continuous dissociation of Fe from the anode. 2+ and Fe 3+ ; S3. Guide the scale-containing catholy liquid away from the electrolysis reactor for physical pre-separation to remove most of the hardness crystal clusters; S4. Mix the physically pre-separated catholy and anolyte, utilizing the automatic acid-base neutralization property of the fluids to adjust the pH back to near neutral, triggering Fe... 2+ Rapid air self-oxidation and subsequent explosive generation of ferric hydroxide polymer network, through electrostatic adsorption and sweeping flocculation network, trap and capture micro-nano scale particles that have not settled completely, colloidal silica and suspended macromolecular organic matter in the water. S5. The mixture from S4 is filtered and collected to retain the flocculated flocs as a flocculant, while clean water is obtained and returned to the main cooling water circulation path.
6. The method for preparing a synergistic flocculant for diaphragm electrolysis dehardening in an industrial circulating water system according to claim 5, characterized in that, The volume ratio of the liquid flowing to the cathode chamber to the liquid flowing to the anode chamber is 6:4 to 9:1, and the residence time in the cathode chamber and anode chamber is between 5 minutes and 20 minutes.
7. The method for preparing a synergistic flocculant for diaphragm electrolysis dehardening in an industrial circulating water system according to claim 5, characterized in that, The anode assembly is made of pure iron plate, low carbon steel plate, cast iron mesh or iron alloy, and the structure is designed as plate solid, multi-layer perforated plate, staggered wire mesh or consumable rod array. The cathode assembly is made of stainless steel, titanium-based materials, high specific surface area carbon felt or graphite felt, and its structure is designed as a three-dimensional mesh structure, multi-layer stacked metal wire mesh or perforated corrugated plate.
8. The method for preparing a synergistic flocculant for diaphragm electrolysis in an industrial circulating water system according to claim 5, characterized in that, The diaphragm is made of porous polymer microporous membrane, ceramic diaphragm, or ion exchange membrane.
9. The method for preparing a synergistic flocculant for diaphragm electrolysis dehardening in an industrial circulating water system according to claim 8, characterized in that, The porous polymer microporous membrane is made of woven mesh or nonwoven nonwoven fabric of polypropylene, polytetrafluoroethylene, polyvinylidene fluoride or polysulfone that has been hydrophilically modified. The average pore size of the cross section must be strictly controlled between 0.05μm and 2.0μm, while the porosity is between 25% and 80%.
10. The method for preparing a synergistic flocculant for diaphragm electrolysis dehardening in an industrial circulating water system according to claim 8, characterized in that, The ceramic diaphragm is an alumina or silicon carbide microporous ceramic diaphragm with controllable pore size; the ion exchange membrane is a cation exchange membrane or an anion exchange membrane.